1953
DOI: 10.1172/jci102706
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Fate of Intravenously Administered Modified Human Globin and Its Effect on Blood Volume. Studies Utilizing I131 Tagged Globin 1

Abstract: The need for blood substitutes adequate to combat the fall in circulating volume in shock continues to stimulate search for high molecular weight compounds which might serve as plasma expanders. Globin, derived from human red blood cells, has been suggested for this purpose (1, 2). While considerable study with this substance is being pursued in various laboratories (1-7), there have been few published reports dealing with its use as a blood volume expander (1). METHODSThe present investigation was approached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

1953
1953
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…Above this level the rate of insulin-I13' degradation decreases significantly, probably as a result of overloading of the insulin degrading mechanisms. A similar decrease in the rate of degradation of P" tagged globulin produced by overloading with large doses of stable globin has previously been reported (16). In the case of insulin, therefore, it appears as if the degradation reaction follows first order kinetics over a very wide range of insulin concentrations.…”
Section: In Vitro Studiessupporting
confidence: 80%
“…Above this level the rate of insulin-I13' degradation decreases significantly, probably as a result of overloading of the insulin degrading mechanisms. A similar decrease in the rate of degradation of P" tagged globulin produced by overloading with large doses of stable globin has previously been reported (16). In the case of insulin, therefore, it appears as if the degradation reaction follows first order kinetics over a very wide range of insulin concentrations.…”
Section: In Vitro Studiessupporting
confidence: 80%
“…Human serum albumin given intravenously has a 50 per cent disappearance time of about five to ten days (17,18). In contrast, the half-life of globin is probably several hours as indicated in the present study and studies utilizing I'll tagged globin (16). Untoward reactions following globin infusions, although frequent in occurrence, were never severe nor harmful in the studies reported here.…”
Section: Methodssupporting
confidence: 45%
“…globin. The rapid disappearance of infused globin from the blood has been noted by others (7,16). In contrast to this, following the daily administration of concentrated human serum albumin the level of albumin in the blood progressively rises and after cessation of administration there follows a slow and progressive decrease (17).…”
Section: Methodsmentioning
confidence: 69%
“…samples of packed erythrocytes, plasma and urine were counted in a well-type scintillation counter with a sensitivity of 1.00 X 106 counts per minute per,c I'l above a background of 200 counts per minute. PBI3s and iodide13 were determined separately utilizing the plasma/RBC ratio of 1131 as previously described (8,9).…”
Section: Methodsmentioning
confidence: 99%